Implementation of CRISPR/Cas9 Genome Editing to Generate Murine Lung Cancer Models That Depict the Mutational Landscape of Human Disease - Hartmann, Oliver; Reissland, Michaela; Maier, Carina R.; Fischer, Thomas; Prieto-Garcia, Cristian; Baluapuri, Apoorva; Schwarz, Jessica; Schmitz, Werner; Garrido-Rodriguez, Martin; Pahor, Nikolett; Davies, Clare C.; Bassermann, Florian; et al. (Frontiers in Cell and Developmental Biology, 2021)
Lung cancer is the most common cancer worldwide and the leading cause for cancer related death among both sexes. Despite the development of novel therapeutic interventions, the 5-year survival rate for NSCLC patients remains low, demonstrating the necessity for novel treatments. One strategy to improve translational research is the development of surrogate models reflecting somatic mutations identified in lung cancer patients as these impact treatment responses. With the advent of CRISPR mediated genome editing, gene deletion as well as site-directed integration of point mutations enabled us to model human malignancies in more detail than ever before possible. Here, we report that, by using CRISPR/Cas9 mediated targeting of Trp53 and KRas, we recapitulated the classic murine NSCLC model, Trp53fl/fl:lsl-KRasG12D/wt. Developing tumors were indistinguishable from Trp53fl/fl:lsl-KRasG12D/wt derived tumors with regard to morphology, marker expression and transcriptional profiles. We demonstrate the applicability of CRISPR for tumor modelling in vivo and ameliorating the need to use conventional genetically engineered mouse models. Furthermore, tumor onset was not only achieved in constitutive Cas9 expressing, but also in wild type animals via infection of lung epithelial cells with two discrete AAVs encoding different parts of the CRISPR machinery. While conventional mouse models require extensive husbandry to integrate new genetic features allowing for gene targeting, basic molecular methods suffice to inflict the desired genetic alterations in vivo. Utilizing the CRISPR toolbox, in vivo cancer research and modelling is rapidly evolving and enables researchers to swiftly develop new, clinically relevant surrogate models for translational research.